Doing internet governance: practices, controversies, infrastructures, and institutions - Dmitry Epstein; Christian Katzenbach; Francesca Musiani (Internet Policy Review, 2016)
This special makes an argument for, and illustrates, the applicability of a science and technology studies (STS) informed approach to internet governance research. The conceptual framework put forward in this editorial and the articles composing this add to the mainstream internet governance scholarship by unpacking macro questions of politics and power. They do so through the analysis of the mundane and taken-for-granted practices and discourses that constitute the design, regulation, maintenance, and use of both technical and institutional arrangements of internet governance. Together, this body of work calls to rethink how we conceptualise both internet and governance.
Keywords: 300; Internet governance; Science and technology studies (STS); Internet infrastructure